Penggunaan Edugame Sebagai Media Pengenalan dan Pengimplementasian Nilai-Nilai Pancasila Pada Anak Kelas 1 SDN Citeureup Mandiri 2 - Annisa Rahmawati Putri R; Ikhfa Fauziyah; Lesta Dwi Agustin; Siti Sofiah A; Maulia Depriya Kembara (Pusat Riset dan Inovasi Nasional, 2024)
Character education is an integral part of early childhood education, especially in introducing the values of Pancasila. This study utilizes a qualitative approach to explore the use of education as a medium for introducing and implementing Pancasila values ​​in first-grade children. The research method involves participatory observation, interviews, and content analysis of educational materials presented to the children. The research findings indicate that the qualitative approach provides insights into how children internalize Pancasila values ​​through various educational activities. The results also highlight the importance of interaction between teachers and students in the learning process, where teachers act as facilitators to reinforce understanding and application of Pancasila values ​​in children's daily lives. The implications of this research emphasize the need for a holistic and child-centered approach in designing effective character education programs that consider the needs and characteristics of individual children.